Effects of hydrocolloids on acorn starch physical properties. (16th March 2016) - Saleh, Mohammed; Ajo, Radwan; Al‐Ismail, Khalid; Ondier, George
Abstract : The effect of hydrocolloids (arabic gum, carrageenan, carboxymethyl cellulose, and xanthan gum) on the physical properties of acorn starch was investigated. First order mixture response surface model was used and the effects of 1% hydrocolloids on acorn starch water holding capacity, starch solution viscosity, gel strength, freeze–thaw stability, and pasting properties were evaluated. Contributions of each hydrocolloid on determining acorn starch functionality were also calculated. Hydrocolloid combinations significantly ( p < 0.05) decrease acorn starch water holding capacity held at 23.3°C from 213.6% of 100% starch to less than 208.3% with minor exceptions. The increase in holding temperature, however, increased water holding capacity (WHC) irrespective of the hydrocolloids set used. The flow behavior indices of treatments ranged from 0.43 to 0.99 and were significantly ( p < 0.05) greater than that of pure acorn starch ( i.e ., 0.66) for most treatments. The consistency coefficient of treatments were significantly ( p < 0.05) greater than that of the control and were best fit for the shear‐thickening model. Significant ( p < 0.05) improvement in gel strength and decrease in freeze–thaw stability of treatments compared to the control was also reported. The pasting properties of treatments increased with the use of hydrocolloids, thus showing the significant role of hydrocolloids in dictating the pasting characteristics of the acorn–hydrocolloids interaction.